The potential for developing a tactile communication system based on Blissymbolics. - Isaacson, Mick D.; Lloyd, Lyle L. (Developmental Neurorehabilitation, 2015)
Objective: To be useful for tactile communication, tactile stimuli need to be discriminable from each other. The objective of this study was to determine whether raised-line renderings of Blissymbols have the capacity for being developed into a tactile communication system as measured by their tactile discriminability. Methods: Tactile discrimination of Blissymbols was measured by performance on a task in which participants were asked to feel a target raised-line Blissymbol and then to find the target within an array containing the target and raised-line Blissymbol foils. Results: The vast majority of tactile Blissymbols had tactile discrimination scores of 90% accuracy or better. Conclusion: Most raised-line Blissymbols can be tactilely discriminated from each other, indicating that they have the potential for being developed into a tactile communication system.